Perancangan dan Analisa Airflow Dust Collector System di PT. Aneka Adhilogam Karya - Nabila Eka Ayunda; Emie Santoso; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The metal casting industry is an activity of processing molten metal material formed in a mould pattern to produce the desired product. Because the gas emissions released during metal smelting have an impact on the safety and health of workers, there is a decrease in air quality and a dust concentration of 1608.30 ?g/m3 is obtained. This value is above the threshold determined by the Decree of the Governor of Central Java no. 8 of 2011 which is 230 ?g/m3. In machining, the entire mould area, and induction furnace are areas that produce a lot of dust particulates. For this reason, it is necessary to design an air filtration system, namely a dust collector system. Dust collector works by sucking dust and air using a pump which is then filtered using a dust filter. The analysis process of this system design will use computational fluid dynamics method. With the analysis of the working system of the machine, it is expected that it will work optimally in air circulation in the metal smelting production building. Then a Cost Budget Plan will also be carried out, in order to estimate the amount of costs required in the installation of the design of the dust collector system. The calculation results in the simulation show that the best performance is in the layout design 2. The suction capacity in the layout design 2 is 13.57 m3/s. These results are not much different from manual calculations or hand calculations.